SAAO small telescopes, capabilities and Challenges. (5th March 2015) - Sefako, Ramotholo
Abstract: The SAAO is at a geographically crucial site in the southern hemisphere between South America and Australasia. SAAO has a long history of involvement in infrared and optical astronomy that dates back almost two hundred years. The observatory expects to continue contributing to astronomical research for many years to come, using its small (0.5m, 0.75m, 1.0m and 1.9m) telescopes and their various instruments (ranging from spectroscopy to polarimetry and high-speed photometry), together with the Southern African Large Telescope (SALT) and other hosted international telescopes. In this paper, I discuss the capabilities and uses of the SAAO small telescopes, and the challenges that threaten astronomical research at the observatory, including light pollution and other emerging threats to the usually dust-free and dark-night-sky site at Sutherland. This is mitigated by the legislation called the Astronomy Geographic Advantage (AGA) Act of 2007 that protects the observatory from these threats.